Floor of mouth thyroglossal duct cyst: a rare embryologic course. Issue 11 (6th November 2019) - Kerr, John; Niermeyer, Weston L; Baker, Peter B; Chiang, Tendy
Abstract: A thyroglossal duct cyst (TGDC) is a common pediatric midline neck mass. Most TGDCs occur in the region of the hyoid bone but have been found less commonly in areas from the oral cavity to the sternum. We present the first reported case of a multifocal floor of mouth (FOM)/cervical TGDC representing an atypical embryonic course. We also review atypical presentations of TGDC and provide a summary of cases involving FOM and multifocal cysts.